PENGARUHKUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA LBPP LIA PEKANBARU - M. Hamdani; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research aims to find out how the influence of product Quality (Reliability, Appearance, Value of the art of a product, product ability to provide service), Promotion (inform, Influence and persuade target customers) and Consumer Satisfaction (Confirmation of hope, repurchase interest, willingness to recommend) On LBPP LIA Pekanbaru. The population in this study are consumers who use the services of English in LBPP LIA Pekanbaru. With 89 samples, sampling using the slovin formula. The data were collected in the form of primary data, with questionnaires distributed as research instrument and secondary data in the form of company archives. Data analysis used was validity test, reliability test, simple linear regression, multiple linear regression, determination test, t test and test F with the help of SPSS program. From result of data analysis covering test of validity, reliability, and multiple linear regression, result of research of t test show calculation of t count (12,928) > t table (1,987) and Sig. (0,000) < 0,05. This means that Product Quality variables significantly influence the Consumer Satisfaction. And result of research show calculation t count (5,025) > t table (1,987) and Sig. (0.000) < 0,05 .This means that Promotion variable have significant effect to Consumer Satisfaction and based on simultaneous test concluded that product quality and promotion together Have a significant effect on consumer satisfaction with big influence 88,456 and F-table equal to 3,10 at LBPP LIA Pekanbaru.Keywords: Product Quality, Promotion, Consumer Satisfaction